The Stringed Musical Instruments - Dialynas, Thanassis (European Journal of Applied Sciences, 2024)
The String – Chord theory is a “mini” mathematical theory which is involved with the propagation of an initial perturbation of the string toward the other parts of the chord (cord) both when its initial shape and velocity is known considered so as an initial value problem (i.v.p.) or as a boundary value problem, (b.v.p.) when the two ends of the cord are kept constant.